Melatonin derivative 6a as a PARP-1 inhibitor for the treatment of Parkinson’s disease - Ma, Qing-Wei; Han, Rui-Ting; Wu, Zi-Jie; Zhou, Jun-Jie; Chen, Meng-Ting; Zhang, Xiang-Zhi; Ma, Wen-Zhe; Feng, Na (Frontiers in Pharmacology, 2024)
Both continuous oxidative stress and poly (ADP-ribose) polymerase 1 (PARP-1) activation occur in neurodegenerative diseases such as Parkinson’s disease. PARP-1 inhibition can reverse mitochondrial damage and has a neuroprotective effect. In a previous study, we synthesized melatonin derivative 6a (MD6a) and reported that it has excellent antioxidant activity and significantly reduces α-synuclein aggregation in Caenorhabditis elegans; however, the underlying mechanism is largely unknown. In the present study, we revealed that MD6a is a potential PARP-1 inhibitor, leading to mammalian targe of rapamycin/heat shock factor 1 signaling downregulation and reducing heat shock protein 4 and 6 expression, thus helping to maintain protein homeostasis and improve mitochondrial function. Together, these findings suggest that MD6a might be a viable candidate for the prevention and treatment of Parkinson’s disease.